2018
DOI: 10.1111/ecc.12840
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality in cancer survivors’ health behaviours-A Danish population-based study

Abstract: The aim of this study was to compare health behaviours (smoking, alcohol consumption, physical activity and diet), to explore social inequality in these behaviours among cancer survivors and individuals with no history of cancer, respectively, and to study the impact of time since diagnosis on cancer survivors' health behaviours. Data from the Danish National Health Survey from 2013 were linked with data from the Danish Cancer Registry to identify all cancer diagnoses among the respondents during the period 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…In our study, the association between higher socioeconomic status and fewer stated needs was seen both in hospital and in the primary care setting. Further, the literature has shown a clear social gradient in cancer survivors’ health behaviors, which emphasizes the need for much more focus on socially differentiated initiatives of cancer survivors [10]. In addition, we recommend special focus on socioeconomically disadvantaged groups when developing initiatives in the field of survivorship care [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the association between higher socioeconomic status and fewer stated needs was seen both in hospital and in the primary care setting. Further, the literature has shown a clear social gradient in cancer survivors’ health behaviors, which emphasizes the need for much more focus on socially differentiated initiatives of cancer survivors [10]. In addition, we recommend special focus on socioeconomically disadvantaged groups when developing initiatives in the field of survivorship care [11].…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, public health systems are based on the citizens’ self-management, like being actively engaged in own treatment and survivorship care and contacting the health system when in need [9]. This organization, however, calls for citizens with surplus energy, and could lead to groups of patients not seeking information or being informed of the possibility for and effect of cancer survivorship care, with the result that they miss out on survivorship care [5, 10-12]. This kind of inequity is argued to be present within cancer survivorship care, since the most exposed patients apparently do not participate in survivorship care in primary care services to the same extent as other patients [4, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the assessment and identification of health behaviors in cancer survivors compared to cancer-free individuals could help them to be aware of their health behaviors and strengthen their prognosis [ 7 ]. Studies have evaluated/identified the differences in health behaviors of cancer survivors compared to cancer-free people in population-based studies, most commonly using techniques such as logistic regression or prevalence ratios [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The most frequently evaluated health behaviors in cancer survivors are alcohol consumption, smoking, and physical activity [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC includes four major types: adenocarcinoma, squamous cell carcinoma, large cell carcinoma, and adenosquamous carcinoma. Age, lifestyle [1], genetic , endocrine [2], occupational exposure [3, 4], and other environmental factors [5] play important roles in lung cancer. In the past years, studies had shown that smoking was the strongest environmental risk factor for the occurrence and development of lung cancer.…”
Section: Introductionmentioning
confidence: 99%